(untitled) (El Taco en la Brea, 2025)
With the aim of exploring the current status of literary criticism as cultural criticism, this dossier brings together advances from ongoing research whose development required interrogating critical moods. Not «states of the art» but «moods» because in recent decades, thanks to Sara Ahmed, we have learned to read «the emotionality of texts», and critical texts are no exception.